Reconstructing Our Orders Artificial Intelligence and Human Society - Jin, Donghan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book discusses in detail the great historical and social significance of the development of Artificial Intelligence (AI). It consists of seven chapters, each focusing on a specific issue related to AI, such as ethical principles, legal regulations, education, employment and security. Adopting a multidisciplinary approach, it appeals to wide readership, ranging from experts and government officials to the general public.
Artificial Intelligence and People's Consensus -- Artificial Intelligence and Ethical Principles -- Artificial Intelligence Governed by Laws and Regulations -- Artificial Intelligence and Employment -- Artificial Intelligence and Education -- Artificial Intelligence and Security -- Artificial Intelligence and International Standards.
Keywords: Computational intelligence; Artificial intelligence; Computers and civilization; Education -- Data processing; Executive power; Security systems; Computational Intelligence; Artificial Intelligence; Computers and Society; Computers and Education; Executive Politics; Security Science and Technology